Circulating Vitamin D Levels in Patients With Systemic Sclerosis: a Meta-Analysis - Lee, Young Ho; Song, Gwan Gyu (Aktuelle Rheumatologie, 2023)
Objective This study aimed to evaluate the relationship between circulating vitamin D levels and systemic sclerosis and to establish an association between vitamin D deficiency and systemic sclerosis.Methods We performed a meta-analysis comparing the plasma/serum vitamin D levels and vitamin D deficiency between patients with systemic sclerosis and healthy controls and examined correlation coefficients between circulating vitamin D levels and the Rodnan score.Results Twenty-one studies involving 1,399 patients with systemic sclerosis and 1,311 controls were included. The systemic sclerosis group had significantly lower vitamin D levels than the control group. Stratification by ethnicity demonstrated significantly decreased vitamin D levels in patients with systemic sclerosis among European, Asian, Arab, Latin American, and mixed populations. Stratification by age, sex, and/or body mass index revealed significantly lower vitamin D levels in the systemic sclerosis group regardless of the adjustment. Subgroup analysis by sample size revealed significantly lower vitamin D levels in the systemic sclerosis group by small (n<100) and large sample numbers (n>100). Stratification by publication year revealed significantly lower vitamin D levels in the systemic sclerosis group in both recent and old publication years. However, no significant difference in vitamin D levels was observed between diffuse and limited types of systemic sclerosis. Vitamin D deficiency was significantly associated with systemic sclerosis. The meta-analysis of correlation coefficients revealed a tendency of inverse correlation between circulating vitamin D levels and the Rodnan score.Conclusions Patients with systemic sclerosis had lower circulating vitamin D levels and higher vitamin D deficiency and there was a tendency of inverse correlation between circulating vitamin D levels and the Rodnan score.
Keywords: vitamin D; autoimmune diseases; systemic sclerosis; malnutrition